2003
DOI: 10.1210/en.2002-0197
|View full text |Cite
|
Sign up to set email alerts
|

Female Oxytocin-Deficient Mice Display Enhanced Anxiety-Related Behavior

Abstract: Previous studies have suggested that oxytocin (OT) may be anxiolytic in female laboratory rats and mice. The elevated plus-maze was used to compare anxiety-related behaviors of OT-deficient (OT-/-) and wild-type (OT+/+) mice. Female OT-/- mice displayed increased anxiety-related behavior compared with OT+/+ mice. The percentage of entries (P < 0.0002) and time spent (P < 0.003) in the open arms was less in female OT-/- than OT+/+ mice. Administration of synthetic OT, 2 ng by intracerebroventricular (icv) injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(120 citation statements)
references
References 27 publications
7
109
1
3
Order By: Relevance
“…[77][78][79] In addition, female OxtÀ/À mice have more, and male mice less, anxiety-like behavior than Oxt þ / þ mice. 77,80 Therefore, it may be that the deficits seen in PCP-disrupted PPI in OxtÀ/À mice are an extension of their overall deficits in cognitive functioning, perhaps reflecting a change in the glutamatergic system, beyond the CSPP.…”
Section: Discussionmentioning
confidence: 99%
“…[77][78][79] In addition, female OxtÀ/À mice have more, and male mice less, anxiety-like behavior than Oxt þ / þ mice. 77,80 Therefore, it may be that the deficits seen in PCP-disrupted PPI in OxtÀ/À mice are an extension of their overall deficits in cognitive functioning, perhaps reflecting a change in the glutamatergic system, beyond the CSPP.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in oxytocin knockout mice have confirmed that these animals have abnormal autonomic and baroreflex control over heart rate (HR) and BP, and that female mice lacking oxytocin have increased anxiety-like behaviors (Mantella, Vollmer, Li, & Amico, 2003;Michelini, Marcelo, Amico, & Morris, 2003). Other recent research in both male and female animal models indicates that in addition to its production within the hypothalamus, oxytocin is produced and released in the heart and the vasculature, and that oxytocin specifically activates receptors that are present in both sites, leading to decreases in HR, contractile force and vascular resistance (Jankowski et al, 2000;Mukaddam-Daher, Yin, Roy, Gutkowska, & Cardinal, 2001;Thibonnier et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…after suspension in a minimal amount of Tween and made up to volume with distilled water. 8-Br-cAMP was prepared in artificial cerebrospinal fluid and injected into the right lateral ventricle (intracerebroventricularly) in a volume of 4 l at a rate of 1 l͞min as described (15). Cyclosporin A was prepared in 50% DMSO.…”
Section: Methodsmentioning
confidence: 99%